Posted by **Susan** on Thursday, August 2, 2007 at 7:52pm.

using quadratic formula 3y2=6+7y

3 y^2 -7y - 6 = 0

When using the quadratic formaul to find y, a = 3, b = -7 and c = -6

y = [-b +/- sqrt (b^2 -4ac)]/2a

= {7 +/- sqrt (49 + 72)}/6

= {7 +/- 11)/6

= +3 or -2/3

## Answer This Question

## Related Questions

- Math using Quadratic equation - The area of a square is 196cm2(squared), find ...
- College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...
- Algebra II - Find the exact solutions to 6x^2+x+4=0 by using the quadratic ...
- Algebra - Explain how to solve a quadratic equation using the quadratic formula.
- algebra - Solve this quadratic equation using the quadratic formula. x^2 + 8x - ...
- math,help,algebra I - I need help can someone help me get unstuck and let me ...
- algebra - Quadratic equations can be solved by graphing,using the quadratic ...
- algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...
- Math - Solve the given quadratic equation exactly using the quadratic formula. ...
- Math - Solve the given quadratic equation exactly using the quadratic formula. ...

More Related Questions